Hydromagnetic mixed convection flow in an inclined cavity - Zainuddin, Najahulfazliah; Sufahani, Suliadi Firdaus; Karimipour, A.; Ali, Mahazani; Roslan, Rozaini (Pushpa Publishing House, 2018)
The effect of inclination angle on the mixed convection in a lid-driven rectangular porous cavity subjected to magnetic field is investigated numerically. The bottom and top walls are kept at hot and cold temperatures, respectively, while the vertical walls are adiabatic. The top wall is subjected to a constant velocity from left to right. The finite volume method with semi-implicit for pressure linked equations (SIMPLE) algorithm is employed to solve the dimensionless governing equations. The numerical results are compared with the reference solution and good agreement is attained. Effects of the inclination angles (), Darcy numbers (Da) and Hartmann numbers (Ha) on the flow and heat transfer are studied. It is evident that the streamlines and isotherms are changed substantially as the cavity filled with porous medium is inclined in the presence of magnetic field.